Adenosquamous carcinoma of the oesophagus in a dog. (27th January 2015) - Okanishi, H.; Shibuya, H.; Miyasaka, T.; Asano, K.; Sato, T.; Watari, T.
<x xml:space="preserve">Abstract</x> A six‐year‐old mixed‐breed male dog weighing 7.0 kg was presented with chronic vomiting and regurgitation. Endoscopic examination revealed prominent oesophageal dilation in the thoracic region, multiple small greyish‐white nodules over the oesophageal lumen and cauliflower‐like masses in the caudal oesophagus. Histopathological studies revealed a characteristic pattern of coexisting elements of infiltrating adenocarcinoma and squamous cell carcinoma. Immunohistochemical staining with anti‐cytokeratin AE1 + AE3 was positive in both types of neoplastic cells. Neoplastic glandular cells stained positively for cytokeratin 8 while neoplastic squamous cells stained positively for cytokeratin 5/6. On the basis of these findings, the dog was diagnosed with oesophageal adenosquamous carcinoma. The case history and findings suggest that the malignancy might have developed from Barrett's oesophagus following irritation of the oesophageal mucosa due to chronic vomiting and regurgitation.